Cancer‐associated somatic DICER1 hotspot mutations cause defective miRNA processing and reverse‐strand expression bias to predominantly mature 3p strands through loss of 5p strand cleavage. Issue 3 (25th January 2013) - Anglesio, MS; Wang, Y; Yang, W; Senz, J; Wan, A; Heravi‐Moussavi, A; Salamanca, C; Maines‐Bandiera, S; Huntsman, DG; Morin, GB
Abstract Our group recently described recurrent somatic mutations of the miRNA processing gene DICER1 in non‐epithelial ovarian cancer. Mutations appeared to be clustered around each of four critical metal‐binding residues in the RNase IIIB domain of DICER1. This domain is responsible for cleavage of the 3′ end of the 5p miRNA strand of a pre‐mRNA hairpin. To investigate the effects of these cancer‐associated 'hotspot' mutations, we engineered mouse DICER1‐deficient ES cells to express wild‐type and an allelic series of the mutant DICER1 variants. Global miRNA and mRNA profiles from cells carrying the metal‐binding site mutations were compared to each other and to wild‐type DICER1. The miRNA and mRNA profiles generated through the expression of the hotspot mutations were virtually identical, and the DICER1 hotspot mutation‐carrying cells were distinct from both wild‐type and DICER1‐deficient cells. Further, miRNA profiles showed that mutant DICER1 results in a dramatic loss in processing of mature 5p miRNA strands but were still able to create 3p strand miRNAs. Messenger RNA (mRNA) profile changes were consistent with the loss of 5p strand miRNAs and showed enriched expression for predicted targets of the lost 5p‐derived miRNAs. We therefore conclude that cancer‐associated somatic hotspot mutations of DICER1, affecting any one of four metal‐binding residues in the RNase IIIB domain, are functionally equivalent with respect to miRNA processing and are hypomorphic alleles, yielding a global loss in processing of mature 5p strand miRNA. We further propose that this resulting 3p strand bias in mature miRNA expression likely underpins the oncogenic potential of these hotspot mutations. Copyright © 2012 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.